Differentiated antiplatelet therapy for acute coronary syndromes - Schaefer, A.; Arntz, H. R.; Boudriot, E.; Garlichs, Christoph; Hoffmann, S.; Ince, H.; Klingenheben, T.; Weil, J.; Zugck, C.; Helms, T. M.; Silber, S. (Deutsche Medizinische Wochenschrift, 2014)
Dual antiplatelet therapy is the cornerstone of maintenance medication following invasive treatment of patients with acute coronary syndromes (ST elevation myocardial infarction, non-ST elevation myocardial infarction, unstable angina). Over the last decade, P2Y12 inhibition in addition to low-dose acetylsalicylic acid has been intensively debated. The debate was enriched by the results of the large phase III clinical trials for prasugrel (TRITON) and ticagrelor (PLATO) compared to clopidogrel in patients with acute coronary syndromes. This article summarizes the critical details und subanalyses of both study programmes and highlights on clinical decision making when using the three P2Y12 blockers in acute coronary syndromes. A special focus is on higher risk patients such as those with ST elevation myocardial infarction and those with coexisting diabetes, but also on minimizing relevant bleedings, which are common during more intense platelet inhibition.
EVALuna2:11996